PENGARUH DUKUNGAN ORGANISASI DAN EFIKASI DIRI TERHADAP KINERJA KARYAWAN PADA PT SINAR SURYA SEHATI - Taat Iman Waruwu; Usran Masahere (Tamilis Synex: Multidimensional Collaboration, 2024)
PT. Sinar Surya Sehati Companies operating in the printing sector (offset printing & packaging) need employees who are consistent in contributing to achieving company targets. Research Design is a research design that will be used as a guideline for carrying out the research process. The purpose of this research is to analyze the influence of Organizational Support and Self-Efficacy on the performance of PT Sinar Surya Sehati employees. This research uses quantitative methodology, which refers to a technique used to evaluate certain theories by analyzing the relationship between variables. This population is 85 employees of PT Sinar Surya Sehati. The sampling used a saturated sampling technique. The approach method in this research uses quantitative methods with observation and questionnaire methods. The data analysis techniques used are Data Quality Test, Classic Assumption Test, Hypothesis Test, and Coefficient of Determination Test (R)2, using SPSS 25. The results of this research show that Organizational Support has a positive and significant effect on employee performance, Self-Efficacy has a positive effect and significantly on employee performance and Organizational Support and self-efficacy together (simultaneously) have a positive and significant effect on employee performance.